Implementation Of Audit Quality Control System Policy on Intern Supervision of The Regional Inspectorate West Sumbawa District - Afriliani, Neni; Zulkieflimansyah, Zulkieflimansyah; Yamin, Ahmad (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
This research discusses the implementation of the Audit Quality Control System Policy in the Internal Supervision of the Regional Inspectorate of West Sumbawa Regency. The aim of this research is to describe the obstacles and implementation of audit quality control system policies in the internal supervision of the Regional Inspectorate of West Sumbawa Regency. The type of research used in this research design uses a qualitative descriptive method with a comparative approach. The research results found that the Implementation of the Audit Quality Control System Policy in the Internal Supervision of the West Sumbawa Regency Regional Inspectorate was based on George C. Edward III's Theory, namely a). Communication: External communication has been carried out in accordance with Audit Standards. Meanwhile, internal communication is still not established intensively. The obstacles found were the lack of persuasive 2 (two) way communication; b). Resources: supporting resources include human resources, budget and facilities and infrastructure. The obstacles found were the lack of fulfillment of these resources in accordance with applicable needs and regulations; c). Disposition or attitude: The auditor is still negligent and not fully objective in carrying out his duties. The obstacles found were the lack of motivation and commitment of the Auditor and insufficient support from APIP Leadership; d). Bureaucratic structure: there is no SOP for implementing audit quality control. The obstacle found is that there has been no development of a quality assurance and improvement program within the scope of APIP. So, it is concluded that the implementation of the Audit Quality Control System Policy in the Internal Supervision of the Regional Inspectorate of West Sumbawa Regency has not been fully implemented properly in accordance with applicable regulations and standards and there are still obstacles found in communication factors, resources, disposition or attitude and organizational structure.